The Impact of Financial Leasing in Profitability of Jordan Commercial and Islamic Banks - Abbad, Jumah; Alkhasawneh, Eyad (The Arab Journal of Administration, 2019)
Leasing is one of the means used in the provision of credit facilities needed to carry out investment projects that require large capital. Where leasing is more flexible and less risky than traditional credit in- struments tool view of the positive advantages enjoyed by comparison to other credit methods. The use of leasing has increased with the increase in economic and investment projects size, which led to the need for this type of credit facilities, both in the commercial banks and Islamic banks. For this study aimed to identify the impact of financial leasing in profitability in Jordan clerical and Islamic banks during the period )2008-2013(In order to achieve the objective of the study a descriptive analytical method was used through building a regression analysis model. The study sample included )9(commercial banks, and )2(Islamic banks, where the data were collected and analyzed using linear regres- sion test, and stability of the data test. The results indicated that there is an impact for financial in the profitability in Jordan commercial and Islamic banks. The study recommended that new researcher must do future research related to financial leasing.